Omega-3 Pathways in Upwelling Systems: The Link to Nitrogen Supply - Puccinelli, Eleonora; Sardenne, Fany; Pecquerie, Laure; Fawcett, Sarah E.; Machu, Eric; Soudant, Philippe (Frontiers in Marine Science, 2021)
Omega-3 long-chain polyunsaturated fatty acids (hereafter, omega-3), including eicosapentaenoic-acid (EPA) and docosahexaenoic-acid (DHA), are essential nutritional compounds for humans, providing several benefits related to cardiovascular and neural health. Human intake of omega-3 occurs mostly via seafood, particularly fish. The primary source of omega-3 in aquatic systems is represented by primary producers, from which omega-3 are transferred throughout the food web. Nitrogen is an essential nutrient for primary producers and can be supplied to surface waters as nitrate upwelled from below, or as ammonium and other regenerated nitrogen forms recycled in situ. Eastern Boundary Upwelling Systems (EBUS) are the most productive marine systems on Earth, together covering only 2% of the ocean’s surface area but supporting 25% of the global fish catch, thereby providing food for humans. In EBUS, nitrate and other nutrients are advected to the surface to support the proliferation of a phytoplankton community dominated by known omega-3 producers (i.e., diatoms). Given current climate change-related projections of ocean warming, acidification, deoxygenation, and increased upwelling intensity, phytoplankton community composition in EBUS may change. Additionally, the global production of EPA + DHA is expected to decrease by up to 30%, rendering its supply for human consumption insufficient by 2050. Here we discuss the state of knowledge related to omega-3 transfer from phytoplankton to small pelagic fish in EBUS, including factors that can influence omega-3 production, links to nitrogen cycling, climate change implications for the omega-3 supply to humans, and suggestions for future research directions to improve our understanding of omega-3 in the ocean.